Structural Aspects of Money Velocity: Errata (Quarterly Journal of Economics, 1960)
In the article, “Structural Aspects of Money Velocity,” by George Garvy appearing in the August 1959 issue the figures in the tables should be corrected to read as follows: In Table II (page 437) the figures for 1954 should be: Individuals, 34.7; Total, holder record, 77.4; Bank and mail float, 17.6; Total, bank record, 95.0. In Table III (page 439) the figures for the following years should be: 1939, 8.54; 1946, 8.70; 1953, 6.16; 1956, 5.61.